Performance of asphaltic concrete modified with recycled crushed bricks - Kharuddin, F. S.; Wan Azahar, W. N. A. W.; Putra Jaya, Ramadhansyah; Mohd Rosli, Hainin; Mohamed Jaafar, Z. F. (IOP Science, 2021)
The pavement industry relies greatly on this conventional material in constructing the road. However, the shortage of the mined material has led to the need of finding alternative with local materials to partially substitute the asphalt components. The conventional pavement industry also contributed to thermal and greenhouse emission resulting from the mining activities. In addition, throughout the year, the amount of construction and demolition (C&D) waste generated from civil construction activities particularly in Malaysia is increasing in alarming rate. Recycling the C&D waste specifically in bricks is viewed as reasonable potential as aggregate modifier in the impulse for greener and sustainable asphalt pavement production. In this paper, recycled crushed bricks (RCB) is introduced to bituminous wearing course as partial replacement for coarse aggregates. The coarse aggregate is partially replaced with RCB in proportions of 0%, 10%, 20%, 30% and 40% by weight. This study summarizes the results of laboratory evaluation of Los Angeles Abrasion Value, Aggregate Crushing Value and Marshall Test. Results show that asphaltic concrete modified with 10% RCB has the lowest abrasion and crushing values which were 20.2% and 30% respectively. Similarly, the mix has the highest Marshall Stability and lowest flow which 15.61 kN and 3.37 mm respectively. Thus, partial replacement of coarse aggregates with 10% RCB in bituminous mix is suitable to be used in wearing course and can be used as alternative material in bituminous mix to reduce the dependency on natural aggregates and utilize the C&D waste efficiently.